(untitled) (Architecture Image Studies, 2021)
Historical structures’ functions may not be sufficient in today’s conditions. Designers’ duty is to support transformations of historical structures that grew multi-layered until today. Purpose of this research is to show that it is possible making contemporary interventions respectful towards original characteristics to prevent them become isolated and to enable sustainable conservation. Interventions show differences due to increasing materials’ variety and improved technologies. These type of interventions especially in Europe have widened. It has become a common practice restoring historical structures using contemporary construction techniques. In the context of the research, the integrity of contemporary interventions in historical environment and the success of these over three cases of Nieto Sobejano Architects’ Office in Europe are analyzed. Nieto&Sobejano Architects is a Spanish oriented architectural office established by Fuensanto Nieto and Enrique Sobejano. In the context, case studies- Moritzburg Museum, Joanneum Museum and San Telmo Museum are discussed. Contemporary interventions are inspected over the design approach criteria, place of addition, formative design criteria and other parameters. Additions of case studies give positive impact on historical structures, promote them to become attraction points in urban context and save them from being isolated by increasing the interest to the structures they are attached to.